2018
DOI: 10.1074/jbc.ra118.003255
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Gli signaling regulates the activity and differentiation of prostate stem and progenitor cells

Abstract: Interactions between cells in the stroma and epithelium facilitate prostate stem cell activity and tissue regeneration capacity. Numerous molecular signal transduction pathways, including the induction of sonic hedgehog (Shh) to activate the Gli transcription factors, are known to mediate the cross-talk of these two cellular compartments. However, the details of how these signaling pathways regulate prostate stem and progenitor cell activity remain elusive. Here we demonstrate that, although cell-autonomous ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Furthermore, Shahi et al found that the Notch signaling plays critical roles in prostate progenitor cells and concluded that Notch signaling is required to modulate the cell cycle and permit normal development and differentiation of prostate spheres [ 56 ]. Consistent with our results, Li et al suggested that cell-autonomous epithelial Shh-Gli signaling and stromal Gli signaling are both essential to the renewal and differentiation potential of epithelial stem and progenitor cells [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Shahi et al found that the Notch signaling plays critical roles in prostate progenitor cells and concluded that Notch signaling is required to modulate the cell cycle and permit normal development and differentiation of prostate spheres [ 56 ]. Consistent with our results, Li et al suggested that cell-autonomous epithelial Shh-Gli signaling and stromal Gli signaling are both essential to the renewal and differentiation potential of epithelial stem and progenitor cells [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…The Hedgehog (Hh) pathway has increasingly been reported to be derepressed in PCA cells under therapeutic treatment, contributing to the progression of CRPC [ 124 , 125 ]. Within the CRPC cells, the higher levels of the Hh pathway ligands (Shh, Ihh, Dhh) promote Smoothed (Smo) derepression, leading to its activation and the consequent activation of Glid, which is a transcription factor [ 124 , 126 , 127 , 128 ]. This Hh pathway plays a central role in cancer stem-cell maintenance, promoting PCA stem cell development, which can contribute to both metastatic progression and chemoresistance [ 126 , 129 , 130 , 131 ].…”
Section: Non-ar Pathwaysmentioning
confidence: 99%
“…Within the CRPC cells, the higher levels of the Hh pathway ligands (Shh, Ihh, Dhh) promote Smoothed (Smo) derepression, leading to its activation and the consequent activation of Glid, which is a transcription factor [ 124 , 126 , 127 , 128 ]. This Hh pathway plays a central role in cancer stem-cell maintenance, promoting PCA stem cell development, which can contribute to both metastatic progression and chemoresistance [ 126 , 129 , 130 , 131 ]. Under conditions of low androgen availability, the abnormal GLI signaling within the epithelial cells contributes to higher levels of p63 expression, resulting in an increase in cancer stem cell activity, facilitating proliferation, metastasis, and resistance to therapeutic intervention [ 129 , 132 , 133 ].…”
Section: Non-ar Pathwaysmentioning
confidence: 99%
“…The expression of Hh signaling components, such as Gli, is also correlated with a higher Gleason score [59][60][61]. During prostate development, Gli signaling is involved in the differentiation of prostate progenitor cells [62], and Gli mediates the oncogenic transformation of prostate basal cells [63]. Furthermore, Gli1 confers basal-like characteristics onto LNCaP cells, leading to the acquisition of PCa hormone independence [64].…”
Section: Hedgehog Signaling and Emi In Prostate Cancer Tumorigenesismentioning
confidence: 99%